Pemanfaatan Media Pop Up Book Materi Cara Menghargai Keragaman Suku Bangsa Budaya di Indonesia untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Kelas 4 SDN Rejosari 01 Semarang - Inayati Inayati; Khusnul Fajriyah; Mintyas Budiastuti (Journal on Education, 2024)
Researchers discovered the problem of low student learning outcomes in material on how to appreciate ethnic and cultural diversity in Indonesia in class 1VB at SD Negeri Rejosari 01 Semarang. The aim of this research is to improve learning outcomes on material on how to appreciate national and cultural diversity through the use of Pop Up Book learning media. Kemmis & Mc Taggart's Classroom Action Research will be used. A total of 26 class IVB students at SD Negeri Rejosari 01 Semarang will be the researcher's observation class. Observation and test assessment sheets are used by researchers in data collection. The minimum class completion size is 75. The results of the research show that there is an increase in better learning outcomes when using Pop Up Book learning media. This is reflected in the average for cycle I of 73% and the proportion increased in cycle II to reach 88%. From the data obtained, it is understood that the learning outcomes of class IV students at SDN Rejosari 01 Semarang will be more focused on learning using Pop Up Book media on material on how to appreciate ethnic and cultural diversity in Indonesia, the subject of Pancasila Education.